'Rowing between two reefs': EFL curricular innovation issues in secondary education in Indonesia - Zifirdaus Adnan; Novi Prihananto (Indonesian Journal of Applied Linguistics, 2022)
This study presents a new look at English curriculum innovations in Indonesian secondary education. Despite the good intention of the designs, many researchers argue that innovations still have not improved school English teaching outcomes. However, little research has examined this issue from the teachers' perspective using a fidelity perspective (Fullan, 2007). This study investigated the 2004 and 2006 English curricula for secondary schools in Indonesia from the English teachers' views using the fidelity framework. It found that the teachers' degree of fidelity was low. They failed to properly implement the critical component: developing students' communicative competencies with the Genre-Based Approach as they substantially adapted the curricula's contents. As suggested in some studies, the failure was not due to their incompetence, although this cannot be entirely discounted. It was more so to external factors beyond their control, especially a mismatch between the amount of material to cover and the time available, inadequate training, and the overwhelming demand to prepare students for the national examination. As the authorities also expected them to implement real innovation, they had to fake their reports. Some implications for future designs and training are suggested.